2022
DOI: 10.3390/cells11152268
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Supplementation Attenuates Ultraviolet-B-Induced Damage Mediated through Elevation of Polyamine Production in Human HaCaT Keratinocytes

Abstract: Magnesium ions (Mg2+) have favorable effects such as the improvement of barrier function and the reduction of inflammation reaction in inflammatory skin diseases. However, its mechanisms have not been fully understood. Microarray analysis has shown that the gene expressions of polyamine synthases are upregulated by MgCl2 supplementation in human HaCaT keratinocytes. Here, we investigated the mechanism and function of polyamine production. The mRNA and protein levels of polyamine synthases were dose-dependently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This result suggests that the change in [Mg 2+ ] cyto is a mitochondria-protective mechanism under oxidative stress conditions. Previous studies have also demonstrated the long-term effects of Mg 2+ on cell protection in keratinocytes 42 and other cells 22 , 24 . [Mg 2+ ] cyto changes the activity of phosphatases, such as mTOR, CREB, and ERK 16 , and leads to cell protection under stress conditions in keratinocytes 42 and neurons 22 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This result suggests that the change in [Mg 2+ ] cyto is a mitochondria-protective mechanism under oxidative stress conditions. Previous studies have also demonstrated the long-term effects of Mg 2+ on cell protection in keratinocytes 42 and other cells 22 , 24 . [Mg 2+ ] cyto changes the activity of phosphatases, such as mTOR, CREB, and ERK 16 , and leads to cell protection under stress conditions in keratinocytes 42 and neurons 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also demonstrated the long-term effects of Mg 2+ on cell protection in keratinocytes 42 and other cells 22 , 24 . [Mg 2+ ] cyto changes the activity of phosphatases, such as mTOR, CREB, and ERK 16 , and leads to cell protection under stress conditions in keratinocytes 42 and neurons 22 . Therefore, Mg 2+ has both acute and long-term protective effects for cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We reported that Mg 2+ treatment of epidermal keratinocytes increases the expression of hyaluronic acid synthase via glycogen synthase kinase 3 and the cyclic AMP response element binding protein, resulting in increased hyaluronic acid production, which promotes wound healing [19]. We also demonstrated that Mg 2+ treatment increases polyamine synthesis and reduces ultraviolet (UVB)-induced cell death in keratinocytes [20]. The above reports suggest that Mg 2+ treatment may have several beneficial effects on epidermal keratinocytes.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, their catabolism involves the enzymes spermine oxidase (SMOX), spermine-/spermidine-N1-acetyltransferase 1 (SAT1) and polyamine oxidase (PAOX), which, as a whole, regulate PAs homeostasis [ 27 ] ( Figure 1 ). Polyamines, among the other biological functions, act as antioxidants and free radical scavengers, therefore contributing to the oxidative balance of the cell [ 25 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%